Labor Supply of Husbands and Wives: A Simultaneous Equations Approach - Lundberg, Shelly (The Review of Economics and Statistics, 1988)
Labor supply functions for married men and women are formulated as a dynamic simultaneous equations system , which is estimated using panel data. Controlling for fixed individu al effects allows marginal labor supply responses to be disentangled from permanent patterns in hours worked due to assortative mating. Th e results suggest that the labor supply of husbands and wives without preschool children is not jointly determined in the short run, while families with young children exhibit strong interactions in work hou rs and negative cross-earnings effects. Neither the joint utility mod el of family labor supply nor an ad hoc "traditional family" model is supported by these results. Copyright 1988 by MIT Press.